Clinical and Angioarchitectural Features of Hemorrhagic Brain Arterio-Venous Malformations in Adults and Children: Contrasts and Implications on Outcome. Issue 4 (16th July 2021) - Qureshi, Ayman M; Muthusami, Prakash; Krings, Timo; Amirabadi, Afsaneh; Radovanovic, Ivan; Dirks, Peter; Shroff, Manohar; Armstrong, Derek; terBrugge, Karel; Pereira, Vitor M
Abstract: BACKGROUND: Hemorrhage from brain arteriovenous malformations (bAVMs) is estimated at 3% per annum. Features influencing risk of hemorrhage include perforator/posterior circulation supply, associated aneurysms, and deep drainage. Children are more likely to present with bAVM bleeds. OBJECTIVE: To analyze differences in bAVM angioarchitecture between children and adults and describe predictors of poor outcome. METHODS: Data were collected from adult and pediatric tertiary referral hospitals. Demographic data, bleed location, treatment, and follow-up modified Rankin Scale (mRS) were collected. Angioarchitectural assessment included aneurysm presence, nidus morphology, perinidal angiogenesis, intranidal shunting, steal phenomenon, venous ectasia, venous stenosis, venous reflux, and pseudophlebitic pattern. Regression analyses conducted to determine predictors of mRS > 2. RESULTS: A total of 270 adult and 135 pediatric ruptured bAVMs were assessed. Median age was 42 (adults) and 10.9 (children) yr. Intranidal aneurysms were more frequent in children ( P  = .012), whereas prenidal aneurysms were more common in adults ( P  < .01). Children demonstrated more perinidal angiogenesis ( P  = .04), whereas steal phenomenon was commoner in adults ( P  < .01). Venous ectasia ( P  < .01), reflux ( P  < .01), and pseudophlebitic pattern ( P  = .012) were more frequent in adults. Children had better outcome (mRS score ≤ 2) ( P  < .01). Older age (odds ratio [OR] = 1.02), eloquent location (OR = 2.5), multicompartmental hemorrhage (OR = 1.98), venous reflux (OR = 2.5), diffuse nidus (OR = 1.83), pseudophlebitic pattern (OR = 1.96), intranidal shunts (OR = 2), and no treatment (OR = 3.68) were significant predictors of mRS > 2. CONCLUSION: Children are more likely to have intranidal aneurysms and perinidal angiogenesis, whereas adults have more prenidal aneurysms, venous ectasia, corticovenous reflux, and pseudophlebitic pattern. Eloquent location, diffuse nidus, intranidal shunts, venous reflux, and pseudophlebitic pattern predict poorer outcome.